Optimalisasi Produksi Bersih dengan Pendekatan Neraca Air di Pabrik Tahu ABC - neldis, flafiana neldis; Rahmawati, Atina (Journal of Industrial Engineering & Technology Innovation, 2024)
Tofu is a food product derived from soybeans. The production process generates waste that can pollute the environment. This study aims to examine clean production methods through direct observation and interviews. The growth of food industry centers, particularly in Wagir, Malang, has intensified competition, often neglecting environmental impacts. Conducted at ABC tofu factory in December 2022, this research investigates the tofu production stages: soaking, washing, grinding, boiling, filtering, coagulating, pressing, molding, and cutting. Notably, ABC factory’s washing process involves flowing water over soybeans soaked for 3 minutes. Water is essential for all stages except molding and is sourced from a well. The factory’s water storage system fills the tank unless manually stopped. At ABC tofu industry, 4350 liters of water are used for 75 kg of soybeans, producing 3813.3 liters of wastewater. Soaking lasts 4-5 hours in a 42 cm diameter and 50 cm height bucket, causing soybeans to swell and soften. Wastewater volume is measured by filtering water from soaked soybeans in a 7-liter bucket; not all soak water is captured during filtration